2017
DOI: 10.1016/j.bbr.2016.09.025
|View full text |Cite
|
Sign up to set email alerts
|

A novel escapable social interaction test reveals that social behavior and mPFC activation during an escapable social encounter are altered by post-weaning social isolation and are dependent on the aggressiveness of the stimulus rat

Abstract: Post-weaning social isolation (PSI) has been shown to increase aggressive behavior and alter medial prefrontal cortex (mPFC) function in social species such as rats. Here we developed a novel escapable social interaction test (ESIT) allowing for the quantification of escape and social behaviors in addition to mPFC activation in response to an aggressive or nonaggressive stimulus rat. Male rats were exposed to 3 weeks of PSI (ISO) or group (GRP) housing, and exposed to 3 trials, with either no trial, all trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 72 publications
2
14
0
Order By: Relevance
“…Additional studies demonstrating social learning processes in the mPFC involve self-reflection, person perception, and theory of mind/mentalizing (Amodio and Frith 2006), understanding self and others, decision making in adults (Heekeren et al 2008), predicting others' preferences (Kang et al 2013), and learning and predicting the likely outcomes of actions of the self and others (Alexander and Brown 2011). Additionally, it has been demonstrated that the mPFC is implicated in facilitating coordination between animals, regulating social interactions, and carrying out complex defensive behaviors (Goodell et al 2017).…”
Section: Mpfc Role In Social Cognition and Learningmentioning
confidence: 99%
See 3 more Smart Citations
“…Additional studies demonstrating social learning processes in the mPFC involve self-reflection, person perception, and theory of mind/mentalizing (Amodio and Frith 2006), understanding self and others, decision making in adults (Heekeren et al 2008), predicting others' preferences (Kang et al 2013), and learning and predicting the likely outcomes of actions of the self and others (Alexander and Brown 2011). Additionally, it has been demonstrated that the mPFC is implicated in facilitating coordination between animals, regulating social interactions, and carrying out complex defensive behaviors (Goodell et al 2017).…”
Section: Mpfc Role In Social Cognition and Learningmentioning
confidence: 99%
“…Recent evidence highlights the mPFC's direct involvement in regulating aggressive behaviors. According to Goodell et al (2017), aggression observed in rodents may be directly associated with changes in mPFC function due to postweaning social isolation (PSI) may be directly related to aggression in rodents that were previously exposed to PSI. Intuitively this would make sense, as emotion regulation and executive functioning are both strongly related to mPFC functionality (Goodell et al 2017).…”
Section: Mpfc Role In Social Cognition and Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…Affected are NMDA receptors in mice after 3 months of social isolation [41], interneurons in mice [42], and central cannabinoid, serotonergic, and cholinergic systems in rats [43]. Aggressive behavior is influenced by social isolation rearing through prefrontal cortex activation [44]. The hippocampus is another brain region that is influenced by social isolation rearing.…”
Section: The Mechanisms Behind Social Isolation Rearing-induced Neuromentioning
confidence: 99%